The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1021/acsami.1c24979
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Nonvolatile Organic Optical Memory Using Self-Assembled Monolayers of Porphyrin–Fullerene Dyads

Abstract: Photo-switchable organic field-effect transistors (OFETs) represent an important platform for designing memory devices for a diverse array of products including security (brand-protection, copy-protection, keyless entry, etc.), credit cards, tickets, and multiple wearable organic electronics applications. Herein, we present a new concept by introducing self-assembled monolayers of donor–acceptor porphyrin–fullerene dyads as light-responsive triggers modulating the electrical characteristics of OFETs and thus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…The technique has been extensively used in the study of silicon materials, for example, photovoltaic devices, and has been suggested as a potential scheme to readout coherent spin states of quantum bits in the semiconductor-based quantum computer concept. [211] The OFET approach discussed above [205] is here extended to qubit measurements with separation between the qubit states and the charge carriers, allowing retention of the spin coherence properties of molecular qubits. One challenge for implementing this readout scheme is the OFET detection of the electric dipole field of the CT state instead of the full charge of a memory element.…”
Section: Field-effect Transistormentioning
confidence: 99%
See 2 more Smart Citations
“…The technique has been extensively used in the study of silicon materials, for example, photovoltaic devices, and has been suggested as a potential scheme to readout coherent spin states of quantum bits in the semiconductor-based quantum computer concept. [211] The OFET approach discussed above [205] is here extended to qubit measurements with separation between the qubit states and the charge carriers, allowing retention of the spin coherence properties of molecular qubits. One challenge for implementing this readout scheme is the OFET detection of the electric dipole field of the CT state instead of the full charge of a memory element.…”
Section: Field-effect Transistormentioning
confidence: 99%
“…Along this line, very recent work has demonstrated that monolayers of D/A porphyrin–fullerene dyads can act as light‐responsive triggers modulating the electrical characteristics of OFETs ( Figure a). [ 205 ] The operational mechanism of these devices has been described as follows. After the absorption of photons by D, photoinduced ET from D to A occurs, thereby generating a CS state.…”
Section: From Sketches To Real Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 More recently, we demonstrated that light-induced isomerization is not needed at all and self-assembled monolayers of the porphyrin-fullerene dyads could enable efficient electrooptical switching of OFETs. 51 While donor-acceptor dyads are known to be highly photoactive, their molecular structures are usually sophisticated and the synthesis is challenging. Therefore, a promising research direction to simplify the structure of the memory OFETs and make their components less expensive would be using some simple organic dyes as receptor components at the semiconductor/dielectric interface instead of donor-acceptor dyads or photochromic molecules.…”
Section: Dsmentioning
confidence: 99%
“…Precise control over the alignment of functional materials is highly desirable in a broad variety of applications including sensors, biomedical electronics, and energy and data storage. Extensive research studies have focused on the photosensitive materials combined with their nanoscale self-assembly in new optoelectronics. Utilizing the versatility and compatibility, prototypes of electronic devices based on a field-effect transistor (FET) architecture were generally reported. Recently, of increasing interest is the phototransistor memory featuring an additional electret for storing and processing optical signals over long-distance transmission with wide bandwidth, high-density data storage, low-power consumption, as well as orthogonal operation in optical/electrical. Therefore, phototransistor memory is regarded to play a pivotal role in exploring next-generation optical communication systems and artificial intelligence. To date, various materials such as nanocomposites, organic–inorganic hybrid perovskites, transition metal dichalcogenides, and liquid-crystalline materials , have been developed for the functional assembly of phototransistors.…”
Section: Introductionmentioning
confidence: 99%